Art and spirituality in environmental education - Grupo de Trabalho e Estudos da Oca-ESAL-USP (Revista Hipótese, 2018)
This article results of a workshop on Art and Spirituality held at the Oca, Laboratory of Environmental Education and Policy-ESALQ-USP for searching collectivelly what would be a "Spirituality of Oca". We started with affective experiences from Gregorian chant, from western spirituality, in dialogue with theoretical references of the environmentalist field. The results demonstrate convergences from the diversity of perceptions, suggesting a transformative potential to Environmental Education.